Contribuição e retrospecto do projeto de extensão universitária Laboratório Móvel de Química - Nobetani, Juliana [UNESP]; Linhares, Ângela Prisca Dias [UNESP]; Santiago, Patrícia Soares [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
With the difficulties faced in Education in Brazil, especially in disadvantaged regions, as in the Vale do Ribeira, students and Unesp Campus Experimental of Registro Professor of Chemistry, Patricia S. Santiago, they decided to investigate how they could contribute to the knowledge produced in the University. Thus in 2012 was born the project "Chemistry Mobile Laboratory" which sought to prepare materials and conduct laboratory practices for chemistry teaching in elementary, middle and high schools of Registro, enabling teachers and students. Knowledge in chemistry at the University, pedagogical guidelines and extension practices were used as a parameter, in its third year of existence we attempted to conduct a retrospective.

Com as dificuldades enfrentadas na área da Educação no Brasil, em especial em regiões carentes, como no caso do Vale do Ribeira, alunos de graduação e a Professora de Química da Unesp Campus Experimental de Registro, Patrícia S. Santiago, decidiram investigar de que forma poderiam contribuir com os conhecimentos produzidos na Universidade. Assim em 2012 nasceu o projeto “Laboratório Móvel de Química” que buscou elaborar materiais e realizar práticas laboratoriais para o ensino de química nas escolas de Ensino Fundamental e Médio de Registro, capacitando professores e alunos. O conhecimento em química da Universidade, orientações pedagógicas e práticas extensionistas foram utilizadas como parâmetro e em seu terceiro ano de existência buscou-se realizar uma retrospectiva.
Keywords: The teaching of chemistry; Electrochemistry kits; Teaching practices; Ensino de química; Kits eletroquímica; Práticas de ensino